Walter Xaver z Dietrichsteina na kavalírské cestě (1683–1688) a jeho boj proti předurčené budoucnosti - Lenka Maršálková (Theatrum Historiae)
Grand tour of Walter Xaver Count of Dietrichstein (1664–1738) seems to be at first sight quite typical but after closer examination, it can not be considered as one of many. By the time he started his journey, Walter Xaver was already the ordained clergyman and his parents supposed that after having completed a demanding educational program, a great spiritual career awaits him. With that, however, this young man had never reconciled and just during his grand tour there was a major turnaround: on his father he gradually acquired not only directing of his education to be more secular but also the promise that in the future he will be allowed to leave the clergy. The presented study therefore notices not only the course of this grand tour, its itinerary and young aristocrat´s educational programme but also building Dietrichstein's ideas about his future, his disputes with his father and the role of the Hofmeister and answers the question whether and how this struggle influenced young man´s studies and his relationships with his parents.